Optimisation of wire-cut EDM process parameter by Grey-based response surface methodology - Amit Kumar; Tarun Soota; Jitendra Kumar (Journal of Industrial Engineering International, 2018)
Wire electric discharge machining (WEDM) is one of the advanced machining processes. Response surface methodology coupled with Grey relation analysis method has been proposed and used to optimise the machining parameters of WEDM. A face centred cubic design is used for conducting experiments on high speed steel (HSS) M2 grade workpiece material. The regression model of significant factors such as pulse-on time, pulse-off time, peak current, and wire feed is considered for optimising the responses variables material removal rate (MRR), surface roughness and Kerf width. The optimal condition of the machining parameter was obtained using the Grey relation grade. ANOVA is applied to determine significance of the input parameters for optimising the Grey relation grade.
Keywords: 650; Wire-cut EDM; Response surface methodology; Grey relation analysis; WEDM